2016
DOI: 10.1097/bcr.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-Performed Hemodynamic Transesophageal Echocardiography in the Burn Intensive Care Unit

Abstract: The use of transesophageal echocardiography (TEE) for resuscitation after burn injury has been reported in small case studies. Conventional TEE is invasive and often requires a subspecialist with a high level of training. The authors report a series of surgeon-performed hemodynamic TEE with an indwelling, less bulky, user-friendly probe. Records of patients treated in a regional burn center who underwent hemodynamic TEE between October 1, 2012 and May 30, 2014 were reviewed. The clinical course of each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Critically ill burned patients are a particular subset of acute trauma patients that pose unique clinical challenges in resuscitation and fluid management due to translocations in volume distribution and fluid shifts resulting in severe shock during the acute phase [ 29 ]. Several resuscitation strategies based on mathematical models that consider a patient’s weight and burn size have been suggested to determine the amount of fluid required for adequate volume resuscitation although there is still debate on its standardization [ 30 ]. Additionally, severe burn patients may present with myocardial dysfunction (both systolic and diastolic) [ 31 , 32 ] and have a higher risk of infections, sepsis, and infective endocarditis.…”
Section: Tee In Severe Burn Injurymentioning
confidence: 99%
“…Critically ill burned patients are a particular subset of acute trauma patients that pose unique clinical challenges in resuscitation and fluid management due to translocations in volume distribution and fluid shifts resulting in severe shock during the acute phase [ 29 ]. Several resuscitation strategies based on mathematical models that consider a patient’s weight and burn size have been suggested to determine the amount of fluid required for adequate volume resuscitation although there is still debate on its standardization [ 30 ]. Additionally, severe burn patients may present with myocardial dysfunction (both systolic and diastolic) [ 31 , 32 ] and have a higher risk of infections, sepsis, and infective endocarditis.…”
Section: Tee In Severe Burn Injurymentioning
confidence: 99%
“…Advanced hemodynamic monitoring is an expanding field of critical care of which some technologies have been studied in burn shock and some have not. Advanced hemodynamic monitoring generally includes modalities such as pulmonary artery catheterization, transpulmonary thermodilution (LiDCO, PiCCO), pulse-contour analysis of the arterial waveform, and echocardiographic evaluation [64]. Two meta-analyses have evaluated mortality with hemodynamic monitoring compared to UOP, and did not demonstrate a conclusive decrease in mortality [56,65].…”
Section: Endpoints Of Resuscitationmentioning
confidence: 99%
“…Cardiac output measurement by ultrasonography may provide additional assessment of preload status, though transthoracic echocardiography can be very challenging in burn-injured patients due to burns to the chest that interfere with image acquisition. Hemodynamic transesophageal echocardiography (hTEE) provides a low-risk means to monitor cardiac preload and contractility real-time throughout the resuscitative period [64].…”
Section: Endpoints Of Resuscitationmentioning
confidence: 99%
“…6 Several studies indicated that the SVC diameter is easily measured with transesophageal echocardiography (TEE) during surgery. [6][7][8] Our study aimed to estimate the effectiveness of the SVC diameter and variation in predicting fluid responsiveness in patients undergoing invasive positive pressure ventilation.…”
mentioning
confidence: 99%
“…In critically ill patients, the SVC variation is an effective indicator for evaluating the intravascular volume status and fluid responsiveness . Several studies indicated that the SVC diameter is easily measured with transesophageal echocardiography (TEE) during surgery . Our study aimed to estimate the effectiveness of the SVC diameter and variation in predicting fluid responsiveness in patients undergoing invasive positive pressure ventilation.…”
mentioning
confidence: 99%